The BnALMT1 and BnALMT2 Genes from Rape Encode Aluminum-Activated Malate Transporters That Enhance the Aluminum Resistance of Plant Cells1 - Ligaba, A.; Katsuhara, M.; Ryan, P.R.; Shibasaka, M.; Matsumoto, H.
The release of organic anions from roots can protect plants from aluminum (Al)toxicity and help them overcome phosphorus (P)deficiency. Our previous findings showed that Al treatment induced malate and citrate efflux from rape (Brassica napus)roots, and that P deficiency did not induce the efflux. Since this response is similar to the malate efflux from wheat (Triticum aestivum)that is controlled by the TaALMT1 gene, we nvestigated whether homologs of TaALMT1 are present in rape and whether they are involved in the release of organic anions. We isolated two TaALMT1 homologs from rape designated BnALMT1 and BnALMT2 (B. napus Al-activated malate transporter). The expression of these genes was induced in roots, but not shoots, by Al treatment but P deficiency had no effect. Several other cations (lanthanum, ytterbium, and erbium)also increased BnALMT1 and BnALMT2 expression in the roots. The function of the BnALMT1 and BnALMT2 proteins was investigated by heterologous expression in cultured tobacco (Nicotiana tabacum)cells and in Xenopus laevis oocytes. Both transfection systems showed an enhanced capacity for malate efflux but not citrate efflux, when exposed to Al. Smaller malate fluxes were also activated by ytterbium and erbium treatment. Transgenic tobacco cells grew significantly better than control cells following an 18 h treatment with Al, indicating that the expression of BnALMT1 and BnALMT2 increased the resistance of these plant cells to Al stress. This report demonstrates that homologs of the TaALMT1 gene from wheat perform similar functions in other species.